Association of hemorrhoidal disease with dementia risk: a nationwide cohort study - Woo, Ho Geol; Park, Moo-Seok; Park, Ju-Young; Chun, Hyejin; Song, Tae-Jin (Frontiers in Neurology, 2025)
IntroductionResearch on the association between hemorrhoidal diseases (HDs) and dementia is limited. We explored this relationship in a population-based longitudinal cohort and proposed that individuals with HD may experience a higher incidence of dementia.MethodsOur study included 381,031 participants drawn from results from the South Korean health-screening cohort database, between 2005 and 2010. HD was identified based on at least two claims using the International Classification of Diseases, Tenth Revision (ICD-10) code I84. We used propensity score matching (PSM) to categorize the participants into two groups based on the presence or treatment of HD. The primary outcome was the incidence of all-cause dementia as determined by two or more claims with ICD-10 codes (F00-03, G30, and G31). Secondary outcomes included the occurrence of Alzheimer’s (F00 or G30) and vascular dementia (F01).ResultsOver a median follow-up period of 15.49 years (interquartile range: 12.21–18.77 years), the cumulative incidence of all-cause dementia was 80,488 cases (22.47%). Multivariate analysis showed that the group with HD consistently had a higher incidence of all-cause dementia than the group without HD after PSM (hazard ratio [HR], 1.243; 95% confidence interval [CI], 1.199–1.288). Participants who underwent surgical procedures or treatment for HD revealed a significantly lower incidence of all-cause dementia after PSM (HR, 0.925; 95% CI, 0.872–0.981).DiscussionThis study revealed a significantly higher incidence of all-cause dementia among participants with hemorrhoidal disease, suggesting that while hemorrhoidal disease may not directly cause dementia, it may serve as a marker of an underlying systemic condition that increases dementia risk.